Do tourniquet and drainage influence fast track in total knee arthroplasty? Our results on 151 cases - Concina, Chiara; Crucil, Marina; Fabbro, Stefano; Gherlinzoni, Franco (Acta Biomedica Atenei Parmensis, 2019)
Background: Fast track in total knee replacement (TKR) is a widely used protocol. Tranexamic acid proved to be effective in reducing perioperative bleeding without increasing thromboembolic risk. The aim of this study was to assess if tourniquet and suction drainage might affect perioperative blood loss and postoperative functional recovery after TKR. Methods: 151 patients, who underwent to TKR, were assessed and divided into three homogeneous groups: group A (51 patients) in which both tourniquet and suction drainage have been applied (tourniquet has been release before wound closure); group B (50 patients) in which neither tourniquet nor suction drainage have been used; group C (50 patients) in which only tourniquet has been used. Perioperative intravenous tranexamic acid and post-operative low-molecular-weight heparin have been administered. Trend of haemoglobin values, transfusion rate, pain, ability to obtain 90 degrees of flexion and length of stay were analysed. Results: The average intra-operative blood loss was statistically higher in group B in comparison to other two groups. Haemoglobin values were lower in group A in comparison to group C in the third and fifth post-operative days. Patients in group A had higher transfusion rate, higher pain and had more difficulties in reaching a 90 degrees of knee flexion than the other two groups. There was one infection in group A. No differences in length of stay. Conclusion: Suction drain seems to be associated to lower haemoglobin values, higher transfusion rate, higher pain and slower functional recovery. Short-term tourniquet does not influence post-operative bleeding and rehabilitation program.